Interdisciplinary Falls Prevention Program for Older Community Dwellers within a Rehabilitation Hospital - Cilia, Simon; Zarb, Edwina; Camenzuli, Michela; Cauchi, Enrica; Cortis, Anabel; Cassar, Ariana-Marie (Magyar Gerontológia, 2024)
Falls are a significant public health concern, particularly among older persons resulting in injuries, decreased mobility, reduced quality of life and higher mortality.